Pengaruh Intensitas Aset Tetap, Ukuran Perusahaan, Dan Profitabilitas Terhadap Penghindaran Pajak (Tax Avoidance) - Mahendra, Arjun; Azis, Azolla Degita; Rizqi , Muhamad Nur (CV. ITTC INDONESIA, 2024)
The purpose of this research is to analyze the influence of fixed asset intensity, company size and profitability on tax avoidance as measured by the Effective Tax Rate (ETR). This research used purpose sampling using certain criteria for construction companies in 2018 - 2022 and obtained a sample of 13 companies with 5 years of observation and obtained 65 observation results. Data analysis in this study used the Eviews 12 program using panel data regression with the selected model comment effect with generalized least squares as a regression tester. The research results show that fixed asset intensity has a positive effect on tax avoidance, company size has a negative effect on tax avoidance, and profitability has no effect on tax avoidance